Kajian Literatur: Gambaran Implementasi Rekam Medis Elektronik di Rumah Sakit Indonesia berdasarkan Permenkes Nomor 24 Tahun 2022 tentang Rekam Medis - Izza, Ania Al; Lailiyah , Syifa'ul (Universitas Airlangga, 2024)
Background: Initially, all medical record documents in hospitals were managed conventionally (manually/written). However, along with the development of advances in information and communication technology and supported by new policies regarding Medical Records contained in the Regulation of the Minister of Health (Permenkes) of the Republic of Indonesia Number 24 of 2022 concerning Medical Records and direct appeals from the Ministry of Health of the Republic of Indonesia, now medical records are starting to shift from conventional to electronic based. Objective: This study aims to determine an overview of the implementation of Electronic Medical Records (RME) in Indonesian hospitals. Method: This research uses a literature review study by searching articles using the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) method. The articles used are national articles searched via Google Scholar using Indonesian keywords, namely the challenges and implementation of electronic medical records in hospitals; challenges or obstacles to electronic medical records in Indonesian hospitals. Key words in English, namely challenges OR barriers to medical records in Indonesian Hospitals; challenges AND implementation of medical records in Indonesian Hospitals. Inclusion criteria were articles on the topic of challenges/barriers/obstacles to implementing electronic medical records in Indonesian hospitals, in the form of quantitative or qualitative research or a combination of both, in Indonesian or English, published between 2016-2023. The exclusion criteria are articles in the form of systematic reviews, literature reviews or community service. Results: Challenges, constraints and barriers experienced by Indonesian hospitals in implementing electronic medical records such as those related to Human Resources (HR), facilities and infrastructure, resistant groups, network connections, no fixed Standard Operating Procedures (SOP), system which sometimes cause errors, financial, and computer and system security. Conclusion: Implementation of Electronic Medical Records (RME) in Indonesian hospitals based on 19 articles that have been analyzed shows that hospitals are not ready to implement Electronic Medical Records (RME). This is supported by the challenges, constraints and obstacles experienced during the process of implementing Electronic Medical Records (RME). The government should directly review the challenges, constraints and obstacles that occur so that the policies issued can be implemented well by all hospitals in Indonesia.